Twin transition in industrial organizations : Conceptualization, implementation framework, and research agenda - Tabares, Sabrina; Parida, Vinit; Chirumalla, Koteshwar (Elsevier, 2025)
The twin transition, which involves the integration of digital and green transformations, is increasingly recognized as crucial for achieving a sustainable and competitive future. These intertwined transitions aim to decarbonize the economy by leveraging advanced digital technologies. Despite growing policy efforts to advance the twin transitions agenda and move toward a net-zero society by 2050, organizations face significant challenges in aligning digital innovations with sustainability goals. These challenges include the lack of a clear conceptualization, foundational success factors, and a structured series of activities needed to achieve the twin transition. These current shortcomings carry practical implications for implementing the twin transition and speak to the need for further research. Consequently, this study addresses these gaps by identifying the factors influencing the organizational implementation of the twin transition. To this end, we conduct a semi-structured literature review to synthesize current research on twin transitions. We provide a novel definition of twin transitions as “two parallel and mutually reinforcing digital and green transitions that amplify each other, leading to sustainable competitiveness for firms”. Moreover, our analysis delineates a twin transition implementation framework, which includes triggers, organizational practices, foundational success factors, and outcomes for organizations. Our findings indicate that twin transitions are manifested through two key organizational practices: the initial stage of twin transition practices and the practices to achieve maturity in the twin transition. Furthermore, the study contributes to the growing literature at the intersection of digitalization and sustainability, providing numerous suggestions for future research and highlighting the importance of focusing on a firm-centric research agenda.
Keywords: win transition; Digital transformation; Twin Transformation; Net-zero industry; Sustainability; green transition; fi=Strateginen johtaminen|en=Strategic Management|